Asthma and smoking-induced airway disease without spirometric COPD. Issue 5 (2nd May 2017) - Thomson, Neil C.
Due to the high prevalence rates of cigarette smoking and asthma, current and ex-smokers frequently develop chronic airway disease without spirometric evidence of chronic obstructive pulmonary disease (COPD), either alone or associated with asthma. This review considers the classification, clinical outcomes, inflammatory and imaging variables, phenotypes, and management of current and ex-smokers with airway disease without COPD, focusing on overlaps in those with and without asthma. These individuals have more respiratory symptoms, worse quality of life, increased exacerbation rates, reduced lung function and more comorbidities than never-smokers with asthma or healthy never-smokers. As well as clinical features, airway inflammatory and structural changes in smoking-induced airway disease without COPD overlap with those found in smokers with asthma. Cigarette smoking is associated with worse clinical outcomes in some phenotypes of asthma. Management involves public health measures to control exposure to tobacco smoke, personal advice on smoking cessation and the use of appropriate targeted therapies, although evidence is limited on their effectiveness. Understanding the mechanisms, natural history and management of current and ex-smokers with asthma and smoking-induced airway disease without COPD is a priority for future research. Cigarette smokers without COPD develop chronic respiratory symptoms due to asthma and smoking-induced airway disease http://ow.ly/rTaS308SLll